2019
DOI: 10.21037/qims.2019.04.18
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance of human functional magnetic resonance imaging: a literature review

Abstract: Background Functional magnetic resonance imaging (fMRI) is one of the most popular methods to probe and understand the human brain, offering a noninvasive way for the in vivo investigation of brain function (1). fMRI accounts for the growth of neuroscience research with some 40,000 peerreviewed publications in the last two decades (2,3). The results of fMRI studies are largely determined by fMRI systems and informatics tools which process complex data generated from fMRI scan. fMRI quality assurance (QA) plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 94 publications
(355 reference statements)
0
25
0
1
Order By: Relevance
“…Others held the view that a minimum sample size of 20 participants per group should be used to obtain 80% power [ 7 ]. It has also been suggested that smaller samples will result in a higher false negative rate [ 8 ], which will require multiple comparison correction to eliminate false positive rates [ 9 ]. There is some consensus among some researchers that to obtain repeatable results and to achieve the stable statistical power, a larger sample size is paramount (at least 40 participants per group) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others held the view that a minimum sample size of 20 participants per group should be used to obtain 80% power [ 7 ]. It has also been suggested that smaller samples will result in a higher false negative rate [ 8 ], which will require multiple comparison correction to eliminate false positive rates [ 9 ]. There is some consensus among some researchers that to obtain repeatable results and to achieve the stable statistical power, a larger sample size is paramount (at least 40 participants per group) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…ECoG requires surgery to fit the electrodes onto the surface of the cortex, making it an invasive technique [40]. MEG [41,42], PET [43][44][45], and fMRI [46][47][48] require very expensive and cumbersome equipment and facilities. Careful development of a set of calibration samples and application of multivariate calibration techniques is essential for near-infrared spectroscopy analytic methods.…”
Section: Bci Systems Classificationmentioning
confidence: 99%
“…The recent advancement of medical imaging has increased attention to the development of image processing methods supporting the diagnosis of diseases. Since Magnetic Resonance (MR) images can be a subject of a variety of image processing operations, including acquisition, compression, reconstruction, or enhancement, their content can be distorted . Furthermore, patient noncompliance or operator mistakes may result in the contamination of acquired images .…”
Section: Introductionmentioning
confidence: 99%